A Multicomponent Health Education Campaign Led by Community Health Workers to Increase Influenza Vaccination among Migrants and Refugees - Ileana Maria Ponce-Gonzalez; Kathleen Perez; Allen D. Cheadle; Morgan Jade; Barry Iverson; Michael Leo Parchman (SAGE Publishing, 2021)
Objectives: To evaluate the impact of a Community Health Worker (CHW)-led influenza campaign on knowledge and attitudes about vaccination in Latinx migrant and refugee populations. Methods: Twelve online workshops were conducted with 183 participants and 24 CHWs between January 12 and May 12, 2021. Participants were Latinx families living in underserved communities throughout Washington state. The initiative also included radio, animated videos, advertisements, social media, and educational materials. Results: Analysis of pre and post workshop surveys from 155 participants showed statistically significant improvements in all questions about the definition of influenza, symptoms, and risks: and in 7 of 9 questions about treatments and vaccines. Analysis of 2 open-ended questions showed increases in words key to understanding influenza, such as "virus," "illness," "death," and "contagious." There were significant increases in rates of participants identifying vaccination and antibiotics as cures for influenza. Conclusions: CHW-led workshops can be an effective way to increase knowledge about influenza and influenza vaccine. Future curriculum should emphasize the difference between viruses and bacteria, and the use of vaccination for prevention as opposed to treatment for illness.